Predictors of perceived pandemic preparedness among general practitioners. (20th October 2021) - Stöcker, A; Demirer, I; Gunkel, S; Hoffmann, J; Mause, L; Ohnhäuser, T; Scholten, N
Abstract: Background: General practitioners (GPs) are essential for providing and maintaining health care during a pandemic. Pandemic preparedness (PP) of GPs can play a vital role in their management of a pandemic situation. This study aimed to examine the association stockpiled personal protective equipment (PPE) and knowledge of pandemic plans on perceived PP among German GPs. This analysis is part of the research project COVID-GAMS (Funding code: 01KI2099). Methods: Three multivariable linear regression models were developed based on an online cross-sectional survey for the period March-April 2020 (the onset of the pandemic in Germany). Data were collected using self-developed items on self-assessed PP and knowledge of a pandemic plan and its utility. The stock of seven PPE items was queried. For PPE items, three different PPE scores were compared. Control variables for all models were gender and age. Results: 508 GPs were included in the study; 65.16% believed that they were very poorly or poorly prepared. Furthermore, 13.83% of GPs were aware of a pandemic plan; 40% rated those plans as beneficial. The stock of FFP-2/3 masks, protective suits, face shields, safety glasses, and medical face masks were mostly considered completely insufficient or insufficient, whereas disposable gloves and disinfectants were considered sufficient or completely sufficient. The stock of PPE was significantly positively associated with PP and had the largest effect on PP across all models; the association of the knowledge of a pandemic plan was significant but considerably smaller. PPE scores did not vary considerably in their explanatory power. The assessment of a pandemic plan as beneficial did not significantly affect PP. Conclusions: An adequate stockpile of PPE is essential for perceived pandemic preparedness among GPs. Pandemic plans are considered less important for GPs. General practitioners, health authorities, and policy makers should focus on stockpiling PPE for future pandemic emergencies. Key messages: Sufficient stockpiled personal protective equipment is the most important factor influencing pandemic preparedness of general practitioners in Germany. Knowledge on a pandemic plan has a subordinate effect on pandemic preparedness of general practitioners; usefulness of a pandemic plan does not have a significant effect.